Efektivitas Herbisida Berbahan Aktif Metil Metsulfuron Terhadap Gulma Pakis Kawat (Dicranopteris linearis) Pada TBM Kelapa Sawit (Elaeis guineensis Jacq) Di Desa Sukoharjo Lahat Sumatera Selatan - Dwi Atmoko; Hartini Hartini (Politeknik Pertanian Negeri Samarinda, 2022)
One of the causes of low oil palm production is the presence of weeds, so weed control efforts are needed. One of the weed control methods is chemical weed control using herbicides. Methyl metsulfuron herbicide is one of the active ingredients of herbicides. The aim of this study was to obtain the optimal dose of methyl metsulfuron to control wire fern weed (Dicranopteris linearis) in immature oil palm plantations. The method used was a randomized block design (RAK) with 8 levels of treatment, namely A (methyl metsulfuron 15 g.b.a/ha), B (methyl metsulfuron 50 g.b.a/ha), C (methyl metsulfuron 85 g.b.a/ha), D (methyl metsulfuron 15). g.b.a/ha + adhesive), E (methyl metsulfuron 50 g.b.a/ha+ adhesive), F (methyl metsulfuron 85 g.b.a/ha+ adhesive), G (manual weeding), H (without control and herbicide). All treatments were replicated 3 times. Parameters observed were weed mortality, weed dry weight and phytotoxicity. Data analysis used linear model variance with a significance of 5%, if there was a significant difference, it was continued with the Ducan Multiple Range Test (DMRT) further test. The results showed that the mortality of Dicranopteris linearis weeds with the herbicide methyl metsulfuron 85 g.b.a/ha was significantly different from the treatment with methyl metsulfuron 15-50 g.b.a/ha. Weed dry weight with the herbicide methyl metsulfuron 15-85 g.b.a/ha and manual control was significantly different from that without control. Weed control with methyl metsulfuron herbicide does not cause phytotoxicity.